Cognitive ability testing for employee selection: implications for age discrimination - Naude, Megan N., author; Fisher, Gwen, advisor; Gibbons, Alyssa, committee member; Rhodes, Matthew, committee member; Henle, Chris, committee member (Colorado State University. Libraries, 2018)
Existing theory and empirical research suggest that tests of fluid cognitive abilities have the potential to lead to age-based adverse impact and may be stronger predictors of job performance for younger job candidates compared to older job candidates. However, the evidence suggests that tests of crystallized cognitive abilities are not as susceptible to age-based adverse impact issues and should be strong predictors of job performance for candidates of any age. The two present studies used cognitive ability test scores collected from management employees in a large company in the United States in conjunction with supervisory performance ratings to examine adverse impact based on age, linear relations of test scores with age, and differential validity and prediction based on age. In the first study, a sample of N = 214 employees completed a test of fluid cognitive abilities, and in the second study, a sample of N = 232 employees completed a test of crystallized cognitive abilities. Contrary to hypotheses, results indicated that age-based adverse impact was more likely to be present for the test of crystallized abilities, age was negatively related to test performance for both tests, and neither test resulted in significant differential validity or prediction for the two age subgroups. Implications for theory and practice are discussed.
Keywords: assessment; selection; cognitive ability; age discrimination